Elucidation of proliferative capability of mononuclear tetraploid cells, emerging spontaneously from diploid cells, using image cytometry and fluorescence in situ hybridization. (22nd May 2013) - Ito, Hideaki; Oga, Atsunori; Furuya, Tomoko; Ikemoto, Kenzo; Amakawa, Genta; Chochi, Yasuyo; Kawauchi, Shigeto; Sasaki, Kohsuke
Abstract: Objectives: Proliferation of tetraploid cells (TCs) emerging from diploid cells is considered to be a critical event toward tumourigenesis, or cancer progression. Recently, several studies have reported that binuclear TCs emerging from normal cells are capable of mitosis, however, it has not been confirmed directly whether mononuclear TCs emerging from normal cells could proliferate, even cancer cells. The aim of this study is to detect mononuclear TCs in vitro, spontaneously emerging from diploid cells and to elucidate their proliferative capability directly. For this purpose, we have developed a novel method. Materials and methods: In this study, two completely disomic cell lines were used, TIG‐7, a fibroblast cell line and CAL‐51, a breast cancer cell line. Cells were cultured on microscope slides and their DNA content was determined using an image cytometer. On the same slides, chromosome numbers were scored using centromere fluorescence in situ hybridization (FISH). For evaluating proliferative capability of TCs, bromodeoxyuridine (BrdUrd) incorporation and colony‐forming ability were examined. Results: Using our method, spontaneous emergence of mononuclear TCs was detected in both TIG‐7 and CAL‐51. Colonies of TIG‐7 TCs were not observed, but were observed of CAL‐51 TCs. Conclusions: Our method enables detection of mononuclear TCs and elucidation of their proliferative capability, directly; this evidence reveals that mononuclear TIG‐7 TCs do not proliferate but that mononuclear CAL‐51 TCs are able to.